Psychometric properties and invariance of the self-efficacy for writing scale in Peruvian high school students - León-Gutiérrez, Matilde; Morales-García, Wilter C.; Morales-García, Mardel; Jaimes-Soncco, Jania; Saintila, Jacksaint; Mamani, Percy G. Ruiz (Frontiers in Education, 2023)
Being able to write is a key competency in educational models; therefore, it is important to have a scale to assess writing self-efficacy. The study evaluated the internal structure, provide evidence of reliability, validity, and factorial invariance of the self-efficacy for writing scale (SEWS) across gender and age in Peruvian schoolchildren. An instrumental study was carried out in 1107 Peruvian adolescents (early, middle, and late) of school age. A confirmatory factor analysis was carried out and the factorial invariance for sex and age was evaluated. A good fit was obtained for the total sample (χ2 = 1229.08, df=101; CFI = 0.997, TLI = 0.997, RMSEA = 0.057 [90% CI: 0.054-0.059], SRMR = 0.029) and presented good α, ω, H reliability (>0.89). Correlations between another measure of writing self-efficacy (p = 0.76; p < .01), study satisfaction (p = 0.31; p < .01), and Burnout (p= -0.12; p < .01) scales supported convergent and concurrent validity. Multigroup factor analysis supported strict invariance for gender and age, for which the SEWS provides evidence of validity and reliability. This adaptation of the SEWS is a valid, reliable, and invariant measure that can be considered for assessing self-efficacy for writing in Peruvian high school students.